MAJOR DEPRESSIVE DISORDER WITHOUT PSYCHOTIC SYMPTOMS IN CHILDREN UNDER THE AGE OF 14 YEAR-OLD RAPE VICTIM. - Andika Metrisiawan (Universitas Udayana, 2014)
Depression is a very large impact on the global disease that affects people worldwide.Lately, an estimated 350 million people suffering from depression. The World MentalHealth Survey in 17 countries stated that 1 in 20 people who reported experiencing adepressive episode in the last 1 year. Depressive disorders often appear early in life andcauses a decrease in a person's interest and often recurrent. For this reason it is said thatdepression is the leading cause of disability in relation to total annual loss due to disability.Therapy should be given a basic psychosocial support combined with antidepressantmedication or psychotherapy such as cognitive behavioral therapy, interpersonal psychotherapy or problem-solving treatment. This case report discusses the severe depression without psychotic symptoms in children under the age of 14 year-old rapevictim. In addition to the victim made an approach to the development of psychological 1 therapy is also given in the form of Psychotherapy and Pharmacotherapy ie 1 x 20 mgfluoxetine oral and Benzodiazepine 1 x 10 mg orally.